Pengaruh Budaya Kerja dan Komunikasi Internal terhadap Kinerja Pegawai pada Dinas Perkebunan Provinsi Sumatera Selatan - Amelia Nur Intan; Luis Marnisah; Susi Handayani (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of work culture and internal communication on employee performance at the South Sumatra Provincial Plantation Service. The research method used is a quantitative method with a causal associative approach. The population in this study was all 79 State Civil Apparatus (ASN) at the South Sumatra Provincial Plantation Service. The sampling technique used was saturated sampling, thus selecting the entire population. Data were collected through questionnaires, observations, interviews, and literature reviews. Data were then analyzed using multiple linear regression, t-tests, and F-tests. The results indicate that work culture has a positive and significant effect on employee performance, internal communication has a positive and significant effect on employee performance, and simultaneously, work culture and internal communication have a significant effect on employee performance. The conclusion of this study is that the better the work culture and the more effective internal communication, the higher the employee performance at the South Sumatra Provincial Plantation Service.   Keywords: Work Culture, Internal Communication, Employee Performance, Civil Servants